Workplace Violence Experienced by Substitute (Daeri) Drivers and Its Relationship to Depression in Korea - Jung, Pil Kyun (J Korean Med Sci, 2015)
Workplace violence is related to various health effects including mental illness such as anxiety or depression. In this study, the relationship between the experience of workplace violence and depression in substitute drivers in Korea, namely, daeri drivers, was investigated. To assess workplace violence, questions regarding types and frequency of the experience of violence over the past year were asked to the daeri drivers. In order to assess the risk of depression, the Center for Epidemiological Studies Depression Scale was used. Odds ratios with 95% confidence intervals of depression were estimated using multiple logistic regression analysis. All of the daeri drivers had experienced instance of verbal violence while driving and 66 of the drivers (34.1%) had been in such a situation more than once in the past quarter of a year. Sixty-eight daeri drivers (42.2%) had experienced certain type of physical violence over the past year. Compared to daeri drivers who had experienced workplace verbal violence less than 4 times and who had not experienced workplace physical violence over the past year, higher odds ratio was observed in daeri drivers who had experienced workplace verbal violence or physical violence, more than 4 times and more than one time respectively, after adjustment. Experience of verbal or physical type of workplace violence over the past year increased the risk of depression in the daeri drivers. Because violence against drivers can compromise the safety of the driver, the customer, and all the passengers, it is imperative that the safety and health of daeri drivers be highlighted.